Nowa komunikacja polityczna: Twitter Andrzeja Dudy - Pietrzyk, Bartosz (Polityka i Społeczeństwo, 2020)
Social media has created new formats and forms of social activity. Production, receipt of information and communications have integrated themselves introducing a new type of communication activity. The role of social media is so important that any social group can go past them indifferently. This situation also applies to politics. Portals such as Twitter, in addition to the innovative communication formula, have established „one-man relations.” The purpose of this work is to determine the formula by which Andrzej Duda runs his Twitter account. The analysis identifies the collection of the most frequently discussed topics, the most popular news, and ways of using the site by Andrzej Duda. The study used quantitative and qualitative methods, including horizontal analysis and content analysis taking into account the media context and hypertextual structure. The main purpose of the description is a thorough quantitative analysis taking into consideration aspects of qualitative analysis (categories, topics, relationships).